2016
DOI: 10.1016/j.prevetmed.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating interactions between UK horse owners and prescribers of anthelmintics

Abstract: Helminths are common pathogens of equids and anthelmintic resistance is a major issue in cyathostomin species and Parascaris equorum. At the heart of mitigating the impact of increasing anthelmintic resistance levels, is the responsible dissemination and use of these medicines following best practice principles. There is a paucity of information on interactions between horse owners and anthelmintic prescribers and how this shapes control. Here, a study was undertaken to determine opinions and experiences of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 35 publications
(21 reference statements)
3
34
0
Order By: Relevance
“…It is therefore necessary to consider in-depth the reasons why people are behaving in a certain way, in order to help them to change their behaviour. We know from surveys of horse owners that they are interested in de-worming (Stratford et al, 2014b), but these surveys also corroborate more general human behaviour studies in confirming that social norms are a more powerful influence than professional advice; horse owners are more likely to do what everyone else on the yard does than what the veterinary surgeon advises them to do (Stratford et al, 2014b;Easton et al, 2016;Rose Vineer et al, 2017). Anthelmintics are available from a variety of outlets and, contrary to guidelines, are often sold without investigation of which diagnostics have been performed and which product is most appropriate.…”
Section: Effecting Change Barriers To Changing Owner Behavioursupporting
confidence: 57%
See 1 more Smart Citation
“…It is therefore necessary to consider in-depth the reasons why people are behaving in a certain way, in order to help them to change their behaviour. We know from surveys of horse owners that they are interested in de-worming (Stratford et al, 2014b), but these surveys also corroborate more general human behaviour studies in confirming that social norms are a more powerful influence than professional advice; horse owners are more likely to do what everyone else on the yard does than what the veterinary surgeon advises them to do (Stratford et al, 2014b;Easton et al, 2016;Rose Vineer et al, 2017). Anthelmintics are available from a variety of outlets and, contrary to guidelines, are often sold without investigation of which diagnostics have been performed and which product is most appropriate.…”
Section: Effecting Change Barriers To Changing Owner Behavioursupporting
confidence: 57%
“…This makes it easy for owners to obtain the products they think they should be using or cost the least money, rather than the most appropriate product. Most owners indicate that they engage with targeted worming, yet when questioned on what they actually do, the responses indicate that most are still deworming at frequent intervals with the results of FEC failing to guide the need for treatment (Stratford et al, 2014b;Easton et al, 2016). A recent study set out to compare horse owners who reported that they used targeted worming strategies with those that did not, but it proved impossible to differentiate one group from the other by their actions (Hodgkinson et al, unpublished data).…”
Section: Effecting Change Barriers To Changing Owner Behaviourmentioning
confidence: 99%
“…Targeted selective treatment strategies aim to reduce use of anthelmintics by exploiting diagnostics (for example, faecal egg count [FEC] analysis) to identify animals that require treatment to reduce shedding of worm eggs in faeces. In the UK, this has become relatively commonplace in worm control programmes and is of value for detecting nematode eggs but not cestode eggs; the excretion of A. perfoliata eggs is intermittent and eggs are unevenly distributed in faeces resulting in low sensitivity of coprological analysis . To address this, a serum‐based test to diagnose tapeworm was developed and has been commercially available for over a decade .…”
Section: Introductionmentioning
confidence: 99%
“…This regulation was generally applied across the considered study sites and well correlated with the involvement of veterinarians into the drenching scheme design. Recent study in the UK suggests that practitioners may provide useful advice on drug use (Easton et al, 2016) and thus reinforce their role in sustainable parasite control. Such partnerships between veterinarians and horse owners should thus be encouraged in France as 40% of the considered sites designed their own drenching scheme.…”
Section: Discussionmentioning
confidence: 99%
“…These two findings need cautious interpretation and the latter association may be the consequence of identified problematic parasite control by managers who ultimately ask their veterinarians for advice. Recent study in the UK suggests that practitioners may provide useful advice on drug use (Easton et al, 2016) and thus reinforce their role in sustainable parasite control. However, a sub-optimal awareness of veterinarians in integrated management of strongyles in France cannot entirely be ruled-out (SallĂ© and Cabaret, 2015).…”
Section: Discussionmentioning
confidence: 99%